Practical observations from an epidemiological investigation of a measles outbreak in a district of India - Mishra Ashok; Mishra Subodh; Lahariya Chandrakant; Jain Pankaj; Bhadoriya Rahul; Shrivastav Dhiraj; Marathe Neera (Wolters Kluwer Medknow Publications, 2009)
Background: Measles is a major cause of childhood morbidity and mortality, accounting for nearly half of the morbidity associated with global vaccine preventable diseases. Regular outbreaks of Measles are reported in India, of which only a few are investigated. This study was conducted in the Shivpuri District of Madhya Pradesh (India) to investigate and asses various epidemiological factors associated with measles outbreak. Materials and Methods: A cross-sectional study was carried out in 30 randomly selected sub-centers in 8 blocks of the Shivpuri District of Madhya Pradesh, covering 212 villages, selected by cluster sampling. The villages, which had reported measles cases, were extensively investigated by the field teams through extensive house-to-house surveys during 12-19 May 2004. Results: A total of 1204 cases with 14 deaths were reported with an attack rate of 6.2% and a case fatality rate of 1.2%. In this study, 17.7% of the cases reported post-measles complications with diarrhea as the most common post measles complication. The routine measles vaccine and Vitamin A supplementation in the area was also less than 30%. Conclusions: The majority of the cases had occurred in the unvaccinated children and in under 5 year old population. There are repeated outbreaks and a long delay in reporting of the cases. The occurrence of cases, in a reasonable proportion of the vaccinated population, points toward the fact that there is a possibility of a vaccine failure in older children. This study calls for an improved surveillance system, an improvement in the cold chain, and enhancements for measles vaccination if India is to achieve the goal of measles elimination.